EFFECTIVE METHODS IN TEACHING FOREIN LANGUAGE LEXICON (Neo Scientific Peer Reviewed Journal, 2024)
This article is devoted to the issues of teaching using the "ESA" method to increase students' foreign language vocabulary, and ways to motivate students are described.